A Newly Discovered “Bull Head Amulet” from Tell El-Farkha, Egypt - Joanna Dębowska-Ludwin (Studies in Ancient Art and Civilization)
In 2022, a new object fitting the so-called “bull head amulets” category was discovered at Tell el-Farkha in layers related to the late Predynastic period (Naqada IID2-IIIA, hereafter abbreviated as NIID2-NIIIA). Although the object displays all the typical features of the “amulets”, it also possesses some unique characteristics, such as its unusual size and lack of perforation, suggesting its use as a figurine rather than a pendant. Furthermore, the Tell el-Farkha item was discovered in a well-recorded settlement context, proving that such “amulets” do not necessarily belong to burial activities. Apart from the presentation of the find and its place of origin, a more general discussion on this interesting type of early Egyptian item raises various questions about their actual function, significance or interpretation.